Voltage Sensors in Hypokalemic Periodic Paralysis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at the National Hospital, Queen Square, London, UK, conducted automated DNA sequencing of the S4 regions of CACNA1S and SCN4A in 83 patients with hypokalemic periodic paralysis (HypoPP).